Effect of organic nutrient on the biodegradation of hydrocarbon contaminated marine sediment in Malaysia - Zahid, Muhammad Ridzuan (2018)
The effect of organic nutrient on the biodegradation of hydrocarbon contaminated marine sediment in Malaysia were investigated. Biodegradation was assessed in microcosm experiments containing 10%(w/w) of crude oil and either amended with inorganic nutrients (NP), or organic matter in the form of plant-based (Elaeis guineensis) or fish-based nutrient amendments (Scomber australasicus). Hydrocarbon mineralization occur in all treatments, with the highest biodegradation rates occur in S. australasicus supplemented sediments. The addition of S. australasicus have managed to reduce the oil concentration to 48% while the addition of E. guineensis and inorganic NP reduced the final oil concentration to 66% and 63% respectively. Bacterial analyses revealed the presence of Psedomonas aeruginosa that are well known for its ability to degrade n-alkanes and polyaromatic hydrocarbon compounds in the spilled oil.